Advanced intelligence systems and innovation in entrepreneurship - Misra, Sanjay 1971-; Jain, Amit 1977-; Kaushik, Manju 1979-; Banerjee, Chitresh; Singh, Yudhveer 1981- (IGI Global, 2024)
The book provides rigorous research on the formation and implementation of effective strategies and business plans, as well as current studies on the nature, process, and practice of entrepreneurship and innovation in the development, implementation, and application of information technology worldwide.
Keywords: Entrepreneurship; Information technology -- Management; Technological innovations